A rare case of pseudoaneurysm caused by Listeria monocytogenes - Xi, Dee; Luo, Chunhua; Li, Qianyuan; Xu, Shaohua; She, Xingrong; Gao, Yan (Frontiers in Medicine, 2025)
Mycotic aneurysm is rare in clinical practice, but it is dangerous because it may expand rapidly, rupture, and threaten the patient’s life if left untreated. The common pathogens include Staphylococcus, Salmonella, and Streptococcus species. Infection caused by Listeria monocytogenes is very rare, with no more than 40 cases reported worldwide to date. To our knowledge, this is the first case of a pseudoaneurysm in the brachial artery caused by L. monocytogenes. Most previously reported cases involved a single aneurysm; however, the case we report is very different. The patient had a medical history of hypertension and cerebral infarction and suffered from aneurysms and pseudoaneurysms at different sites on more than one occasion. The patient was admitted to our hospital due to a pseudoaneurysm in the brachial artery of the left upper limb. Blood culture suggested the infection was caused by L. monocytogenes. The inflammation was almost controlled after 1 month of antibiotic therapy, after which surgery was performed to remove the pseudoaneurysm and reconstruct the left brachial artery using an autologous great saphenous vein graft. Postoperatively, the patient continued to receive antibiotics and was discharged 1 week later in good condition.